"Ungas möjlighet till självständigt resande" - En utvärdering av on-demand trafik och SkåneFlex som en lösning på att underlätta för barns självständiga mobilitet - Pearce,Rebecka (2025)
The use of public transport has an important role in today's society, in terms of meeting future climate goals. In order to encourage its increased use and to meet future challenges, the importance of human perspectives has increased. Planning for transport equity involves addressing inequalities, prioritizing the needs of vulnerable groups and working towards inclusive and sustainable mobility solutions. Skånetrafikens project SkåneFlex, which is on-demand transport, is one way of planning to meet future challenges and improving accessibility for people in the countryside. This qualitative case study aims to explore how children in Skåne would describe this new way of planning for public transport. In what way does on-demand aspire to and achieve public transport justice? This study shows how limited transport options and long distances in rural areas may restrict children’s freedom. Through interviews and a literature review, analysis suggests that SkåneFlex plays an important role in enabling children's independence and freedom in rural areas. This shows how Skånetrafiken works towards public justice by involving children's perspectives.
Keywords: självständig mobilitet; aktiv resa; on-demand trafik; SkåneFlex; transporträttvisa; transportfattigdom